2011
DOI: 10.3138/carto.46.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Genealogy That Counts: Using Content Analysis to Explore the Evolution of Persuasive Cartography

Abstract: Maps are often used for persuasive purposes. Yet little is known about whether or not different persuasive map producers use similar cartographic techniques or about how such techniques have evolved through time. This article explores the genealogy of persuasive map design by analyzing 256 such maps published since 1800. Quantitative content analysis is used to break down each map among 190 contextual, data, design, and layout variables. Cross-tabulations and descriptive statistics are used to test whether and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…Maps are used to make arguments (Harley 1989;Muehlenhaus 2011a;Wood and Fels 1992). It has been shown that maps play a key role in shaping people's beliefs about their environment and the world around them.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Maps are used to make arguments (Harley 1989;Muehlenhaus 2011a;Wood and Fels 1992). It has been shown that maps play a key role in shaping people's beliefs about their environment and the world around them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, manipulative techniques used to convince consumers about the ubiquity of different mobile phone networks are similar to those found on North American maps from the 1800s showing the breadth of a certain railroad network. Muehlenhaus (2011a) also illustrated that persuasive maps may possess a parallel but distinct genealogy from thematic maps. In many ways, analyzing scientific maps is more straightforward than figuring out how to analyze persuasive maps.…”
mentioning
confidence: 96%
“…The process followed is similar as far as it goes to the Quantitative Content Analysis (QCA) process used by Muehlenhaus (2011) in his investigation of 'persuasive cartography' over history. QCA has rarely been applied to maps, being originally developed for analysis of texts and subsequently adapted for images and videos.…”
Section: Classification Of Relevant Cartoonsmentioning
confidence: 98%
“…In QCA, there is the initial definition of variables sought after in the artefacts being investigated (Muehlenhaus identified 192 variables); these variables are listed with the artefact if they are present (in a process called coding). The data thus generated forms the basis for quantitative analysis of the collection of artefacts (Muehlenhaus 2011), which is beyond the scope of this paper. Out of the 77 cartoons collated, this was how the geographic content was distributed.…”
Section: Classification Of Relevant Cartoonsmentioning
confidence: 99%
“…While content analysis has been used for quite some time in historical geographic analysis [40], its integration into GIScience methods is more recent. Content analysis has been used by geographers to analyze both text documents [41] and maps [42][43][44][45]. Whether used for the analysis of text or visual media, content analysis is useful for the study of patterns emerging in communication artifacts and the process remains much the same: documents are collected, systematic data reduction is carried out using thematic coding, analysis of the codes is conducted, and the results are interpreted [46].…”
Section: Content Analysismentioning
confidence: 99%